MY TINY ONE AND I - NAJMIA, SILMY
Many elements impact an individual's growth and development into an adult. The local environment, meaning the family, is one of the variables that impact individual growth and development. The function of the closest family, particularly parents, is referred to as a component that profoundly impacts individuals since parents are the site where an individual receives education for the first time in life. However, the process of an individual's growth and development might leave a trauma that was left behind in childhood. The trauma then indirectly contributes to an individual's growth process. The inner child is a combination of positive and negative events in a kid's life that might form their personality as adults. According to Dr. Stephen Diamond, the innerchild is a very strong psychological or phenomenological reality related to our subconscious. As a victim of childhood trauma, In her writing and research, the author is driven to address the issue of inner-city children. Its goal is to present and make the writers and audience aware of the significance of childhood trauma. In order to realize it, the author tackles art as expression, psychology of art, theory of psychoanalysis development, and drawing with embroidery methods. The conclusion that can be derived from this work and research is how the author is ultimately able to combine craft and art in the process of creation. The threads stitched on the fabric reveal the drawing hidden within the work. The embroidered threads take the form of a line, and the line is one of the drawing's key features. In that way, the line is an abstract mark that may be found in every trace of human existence and activity. The final form rendered is a work of art by including the author's personal and self-expression.Key words : Innerchild, drawing, art and craft.